Development of Mama Lala healthy food 's Healthy Food Catering Kitchen Business Expansion in Tangerang - Aliwarga, Glenn Richard; Kurnia, Mikha Eliazer; Kovalenko, Neswa; Sanjaya, Yoel (Corespub, 2025)
This study aims to explore the strengths of Mama Lala healthy food’s Kitchen as an affordable catering service provider, offering customizable menu options and free delivery. The identified issue is the large number of catering providers unable to meet customer demands for competitive pricing, menu flexibility, and efficient delivery. The study seeks to understand how Mama Lala healthy food ’s Kitchen can meet these market needs. A qualitative research approach was used, including in-depth interviews with customers and managers of Mama Lala healthy food ’s Kitchen, as well as observations of business operations and an analysis of competitor pricing and services. The results show that Mama Lala healthy food ’s Kitchen successfully attracts customers with more competitive prices compared to its competitors, along with a menu that can be tailored to individual needs. Free delivery within a 15 km radius is also a valued benefit by consumers. These strengths give Mama Lala healthy food ’s Kitchen a strategic position in the local catering market. The implications of this study highlight the importance of maintaining the quality of raw materials, menu diversity, and free delivery services as key attractions to stay competitive. The study also suggests that Mama Lala healthy food ’s Kitchen expand its network and enhance its promotional efforts to increase awareness among potential customers.